Association between anemia and stroke with its subtypes in adults : Insights from NHANES 2005–2016 and Mendelian randomization analyses - Li, Qizhao; Wang, Shuai; Gao, Wenjuan; Wei, Yuying; Gao, Xiao; Wang, Puzhou; Rebetz, Johan ; 0000-0003-1673-0684; Semple, Elisabeth; Guo, Li; Semple, John W.; Martínez-López, Joaquín; Peng, Jun; et al. (Experimental Gerontology, 2025)
Stroke and anemia are both prevalent conditions with significant health burdens, yet their bidirectional relationship remains poorly understood. Anemia affects up to 29 % of stroke patients and is associated with increased worse outcomes. However, the causal nature of this association, particularly concerning different anemia subtypes, remains controversial, and there is a lack of clear targets and specific treatments for anemia in stroke patients. This study employed data from National Health and Nutrition Examination Survey (NHANES) database and two sample Mendelian randomization (MR) to investigate the relationship between different types of anemia, particularly aplastic anemia (AA) and iron deficiency anemia (IDA), and the risk of stroke and its subtypes in adults. The study included 7931 participants (3824 male and 4107 female) from NHANES (2005–2016). After adjusting for all covariates, the exposure factor of stroke was significantly positively correlated with the risk of anemia in middle-aged and elderly females, while in males, although the correlation was not significant, it was close to the threshold (OR = 1.66, 95 % CI = 0.987–2.78, P = 0.0558 in male. OR = 2.36, 95 % CI = 1.35–4.14, P < 0.01 in female at model 3). Genetically instrumented total anemia risk was nominally associated with risk of stroke (P = 0.086), IDA (OR = 1.413, ARI = 0.0407, 95 % CI = 1.318–1.515, P < 0.001) and AA (OR = 1.057, ARI = 0.0058, 95 % CI = 1.002–1.116, P = 0.04) were significantly associated with stroke risk. Furthermore, both genetic instrumented IDA and AA were significantly associated with an increased risk of large artery stroke but not with other stroke subtypes, in a unidirectional manner. The reverse MR analyses showed that genetically predicted stroke risk also associated with increased risk of total anemia (OR = 1.005, ARI =0.0050, 95 % CI = 1.003–1.007, P < 0.001), as well as with subtypes of anemia (IDA: OR = 1.038, ARI =0.0366, 95 % CI = 1.002–1.075, P = 0.037; AA: OR = 1.240, ARI =0.1935, 95 % CI = 1.062–1.447, P = 0.012). In conclusion, a bidirectional association between increased risk of two types of anemia and elevated stroke risk was observed, with varying magnitudes of effect. Randomized trials are now needed to assess the effects of different treatments for anemia on stroke and its subtypes, particularly in high-risk older individuals.
Keywords: Anemia; Aplastic anemia; Iron-deficiency anemia; Mendelian randomization; NHANES; Risk factor; Stroke; The middle-aged and the elderly